Effect of biomass ash addition on coal ash fusion process under CO2 atmosphere. (1st November 2018) - Qin, Yu-hong; Feng, Min-min; Zhao, Zi-bing; Vassilev, Stanislav V.; Feng, Jie; Vassileva, Christina G.; Li, Wen-ying
Graphical abstract: Highlights: Biomass addition to coal increases the initial formation of liquid phase in ash. Coal ash with rice straw ash addition ≤3 wt% fits to softening-melting mechanism. Coal ash with rice straw ash addition >3 wt% fits to melting-dissolution mechanism. Abstract: The ash fusion process of Jincheng anthracite ash, rice straw ash and coal-biomass ashes with different rice straw ash addition ratios during co-gasification under CO2 atmosphere was elucidated by the ash fusion test, chemical analyses, optical heating stage microscopy (OHSM), X-ray diffraction and scanning electron microscopy equipped with energy-dispersive X-ray analyzer. Results showed that the initial sintering and initial melting temperatures of coal-biomass ashes observed by OHSM decreased with the addition of rice straw ash. The deformation temperatures determined by the ash fusion test were close to the initial melting temperatures. The biomass ash addition to coal ash introduced excessive amounts of alkaline compounds in the ash mixtures that led to lower initial temperatures of liquid phase formation. The ash fusion behavior of coal-biomass ashes with a rice straw ash addition ≤3 wt% was similar to that of coal ash and fits to the "softening-melting" ash fusion mechanism. In contrast, the ash fusion behavior of coal-biomass ashes with a greater addition of rice straw ash (>3 wt%) experienced dramatic changes at lower temperature and fits to the ''melting-dissolution'' ash fusion mechanism.